Linguistic Contextualism of the Cambridge School: The Problem of the Idea as Historical Action - Georgiy R. Khudaybergenov (RUDN Journal of Political Science)
This study critically analyses The Cambridge School’s linguistic contextualism, focusing on the work of John Pocock and Quentin Skinner, in order to identify the limitations of this approach to the writing of intellectual history. The author questions the primacy of linguistic context in text interpretation postulated by The Cambridge School, suggesting that the movement of ideas should be seen not only as an integral part of the speech acts that generate them, but also as determined primarily by social conditions. The article discusses in detail the main provisions of linguistic contextualism: the concept of discourse as a system of linguistic conventions that define the boundaries of possible utterance; the role of speech act as an instrument of discourse change and political action; and the significance of authorial intention in text interpretation. By analysing the key works of Pocock and Skinner, the author identifies a number of problematic points in their methodology. In particular, the idea of the autonomy of language is criticised, which, in the author’s opinion, fails to fully account for the influence of social context on the formation and development of ideas. Relying on the concept of the speech act as a form of social practice based on the principles of dialectical materialism, the author proposes to expand the methodological toolkit of The Cambridge School. In particular, he insists on the paramount need to analyse the material and social conditions in which discourse is produced. This will allow, in the author’s opinion, to overcome the limitations of linguistic contextualism and create a more adequate tool for writing intellectual history. The author concludes the article by outlining the prospects for further research in this direction, emphasising the importance of a consistent critical synthesis of productive methodological approaches for a deeper understanding of the relationship between language, thought and social reality.